Wearable Graphene Sensor for Pulse Measurement - Vićentić, Teodora; Rašljić Rafajilović, Milena; Koteska, Bojana; Madevska Bogdanova, Ana; Pašti, Igor; Spasenović, Marko (Institute of Technical Sciences of SASA, 2021)
Graphene is a material that has been widely used in different types of sensors, due to its optimal electrical and mechanical properties. Recently discovered laser-induced graphene (LIG) has opened new perspectives for a versatile and durable physical sensing platform, capable of detecting various physical parameters. In this study, LIG was produced by CO2 laser irradiation of polyimide film. LIG-based sensor was used to measure human pulse. Fabricated LIG sensors were attached to a subject’s body. A temporal change in resistance was recorded for different sensor embodiments, including as-fabricated on polyimide tape and transferred into a PDMS matrix. The measured change in resistance is induced by bending of the sensor due to vein pulsing. The measured resistance time traces were analyzed with the Python HeartPy module to extract pulse information, demonstrating agreement with commercially available sensors.